1976
DOI: 10.1007/bf02533051
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐function activity of azasterols and nitrogen‐containing steroids

Abstract: Thirty-nine nitrogen-containing steroids were tested against two gram-negative, five gram-positive, and two yeast organisms. Many of these steroids have been previously reported to inhibit various metabolic processes involving sterol metabolism. While low minimal inhibitory concentration (MIC) values were recorded for sterol producing yeast, growth of bacteria which contain no sterols was also inhibited. Structure-function studies provided no relationship between biological activity and hypocholesteremic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Our theoretical research supports early studies on the action mechanisms of amino and azasteroids that was presumed that these compounds act due to a more fundamental mode than on sterol metabolism alone, interfering with mitochondrial respiration and/or oxidative phosphorylation [41]. Computer modeling prediction of steroidal compounds metabolism by CYP3A4 with has been documented in several studies [42][43][44].…”
Section: Discussionsupporting
confidence: 59%
“…Our theoretical research supports early studies on the action mechanisms of amino and azasteroids that was presumed that these compounds act due to a more fundamental mode than on sterol metabolism alone, interfering with mitochondrial respiration and/or oxidative phosphorylation [41]. Computer modeling prediction of steroidal compounds metabolism by CYP3A4 with has been documented in several studies [42][43][44].…”
Section: Discussionsupporting
confidence: 59%
“…In early studies on the action mechanisms of amino and azasteroids it was presumed that these compounds act because of a more fundamental mode than on sterol metabolism alone, interfering with mitochondrial respiration and/or oxidative phosphorylation (Kabara et al , 1976). Trafalis et al (1995) first reported the stimulatory effect of two steroid lactams (homo‐aza‐steroids) on the proliferation of non‐lymphocytic leukaemia blast cells that possibly was produced through PKC system induction.…”
Section: Discussionmentioning
confidence: 99%